2019
DOI: 10.1055/s-0039-3402825
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Deferred Revascularization Following Physiological Coronary Assessment Using Fractional Flow Reserve

Abstract: Objective Outcomes of patients with deferred revascularization for intermediate stenosis coronary lesion based upon physiological assessment using fractional flow reserve ([FFR] >0.80). Methods Patients with chest pain with angiographic intermediate stenosis, (40–70% stenosis) without noninvasive test evidence of ischemia were selected and underwent an FFR assessment between January 1, 2015, and August 31, 2018. Patients with intermediate lesions of FFR > 0.80 were followed, and those patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…The three important randomized controlled trails on FFR (FAME-2, 5 DANAMI-3-PRIMULTI, 6 and COMPARE-ACUTE 7 ), where deferred revascularization depending on the FFR value, showed that it was safer, even though the last two trials were done in acute coronary syndrome (ACS) patients. On contrary, this present study 8 shows that the incidence of target lesion failure in intermediate stenosis with deferred revascularization (FFR > 0.8) was high (5.8%).…”
Section: Conflict Of Interestcontrasting
confidence: 99%
See 1 more Smart Citation
“…The three important randomized controlled trails on FFR (FAME-2, 5 DANAMI-3-PRIMULTI, 6 and COMPARE-ACUTE 7 ), where deferred revascularization depending on the FFR value, showed that it was safer, even though the last two trials were done in acute coronary syndrome (ACS) patients. On contrary, this present study 8 shows that the incidence of target lesion failure in intermediate stenosis with deferred revascularization (FFR > 0.8) was high (5.8%).…”
Section: Conflict Of Interestcontrasting
confidence: 99%
“…Shabbir et al, 8 in their study, suggested that predicting 1-year rates of deferred lesion intervention (DLI) based on simple characteristics available at the time of index FFR measurement was presence of diabetes mellitus, left ventricular dysfunction, and ACS presentation. But this proposition is also controversial.…”
Section: Conflict Of Interestmentioning
confidence: 99%